Trends in Indicators of Injection Drug Use, Indian Health Service, 2010-2014: A Study of Health Care Encounter Data. (July 2020) - Evans, Mary E.; Person, Marissa; Reilley, Brigg; Leston, Jessica; Haverkate, Richard; McCollum, Jeffrey T.; Apostolou, Andria; Bohm, Michele K.; Van Handel, Michelle; Bixler, Danae; Mitsch, Andrew J.; Haberling, Dana L.; et al.
Objectives: Hepatitis C virus (HCV) and HIV transmission in the United States may increase as a result of increasing rates of opioid use disorder (OUD) and associated injection drug use (IDU). Epidemiologic trends among American Indian/Alaska Native (AI/AN) persons are not well known. Methods: We analyzed 2010-2014 Indian Health Service data on health care encounters to assess regional and temporal trends in IDU indicators among adults aged ≥18 years. IDU indicators included acute or chronic HCV infection (only among adults aged 18-35 years), arm cellulitis and abscess, OUD, and opioid-related overdose. We calculated rates per 10 000 AI/AN adults for each IDU indicator overall and stratified by sex, age group, and region and evaluated rate ratios and trends by using Poisson regression analysis. Results: Rates of HCV infection among adults aged 18-35 increased 9.4% per year, and rates of OUD among all adults increased 13.3% per year from 2010 to 2014. The rate of HCV infection among young women was approximately 1.3 times that among young men. Rates of opioid-related overdose among adults aged <50 years were approximately 1.4 times the rates among adults aged ≥50 years. Among young adults with HCV infection, 25.6% had concurrent OUD. Among all adults with arm cellulitis and abscess, 5.6% had concurrent OUD. Conclusions: Rates of HCV infection and OUD increased significantly in the AI/AN population. Strengthened public health efforts could ensure that AI/AN communities can address increasing needs for culturally appropriate interventions, including comprehensive syringe services programs, medication-assisted treatment, and opioid-related overdose prevention and can meet the growing need for treatment of HCV infection.